The Effect of Poster Media on Fourth-Grade Students’ Learning Interest in Indonesian Language at MIS Babul Ilmiy Rumbia - Resti; Nurhaedah; Andi Dewi Riang Tati (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study was conducted to examine the effect of poster media on fourth-grade students’ learning interest in Indonesian Language at MIS Babul Ilmiy Rumbia, Jeneponto Regency. This research employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The population and sample consisted of 13 fourth-grade students selected through saturated sampling. Data were collected using observation sheets and a learning interest questionnaire based on four indicators: attention, interest, enjoyment, and participation. The results of descriptive analysis showed that the implementation of poster media was categorized as good (87%), indicating that the learning process was carried out effectively. The average score of students’ learning interest increased from 66.62 (pretest) to 82.31 (posttest). Inferential analysis using a paired-sample t-test revealed a significant difference between pretest and posttest scores (t = 17.139; Sig. = 0.000 < 0.05). These findings indicate that the use of poster media has a significant positive effect on students’ learning interest. Therefore, poster media can be considered an effective instructional tool to enhance student engagement and create a more interactive learning environment in elementary education.